Anemia in Peru: is there a need for universal supplementation and food fortification with iron? - Bustamante, Ernesto (2025)
For over 60 years the World Health Organization (WHO) has recommended iron supplementation for vulnerable populations in low- and middle-income countries due to the high prevalence of anemia. Despite these measures, childhood anemia remains a serious public health issue. Governments have implemented policies such as iron supplementation and food fortification, but the results have been limited. Advances in the understanding of iron physiology—particularly regarding regulatory hormones and the risks associated with excessive intake—have led to a rethinking of current approaches. In 2024, the WHO updated the hemoglobin thresholds for defining anemia, which has changed the global landscape. In Peru, this revision reduced the prevalence of anemia in children aged 6 to 35 months to 35,3%, meaning it is no longer considered a severe public health problem. This calls for a reassessment of the universal nature of current intervention strategies.